Orientation and directional escape by Blanchard’s Cricket Frog, Acris blanchardi (Amphibia: Anura: Hylidae), in response to a human predator - McCallum, Malcolm (Acta Herpetologica, 2011)
I investigated the seemingly haphazard jumping pattern of Blanchard’s Cricket Frog (Acris blanchardi) to determine if it was random or patterned. I approached frogs from the front (cranial), back (caudal), and side (lateral) simulating an attacking predator. On average, frogs jumped away at 135.73° (SE = 2.31°) from the direction of attack. I did not distinguish between right and left directions in this study. There were significant differences in the angle of escape among the three attack directions (F2,87 = 17.64, P < 0.001). There were no significant differences in escape angle between frogs that I approached from the front (mean = 130.4°, SE = 2.59°) or the side (mean = 126.3°, SE = 3.75°, Tukey interval: -0.261, 0.626). The angle of escape was not uniform and directional escape was around 120° across all tests. Frontal and side approaches led to escape angles near 120° but attacks from the rear resulted in two modes of escape, at about 180° and 120° from the angle of approach. These frogs have a possible blind spot in the rear of their field of vision that might explain this bimodal escape pattern in rear attacks. The tendency to jump away at an angle rather than strait away from the predator likely represents as an evolutionary compromise between an attempt to maximize angular and linear displacement from the attacking predator. This optimal strategy may demonstrate a fitness and survival advantage.